Understanding Cardiopulmonary Resuscitation Determines the Readiness of Doing Basic Life Support - April Poerwanto; Agus Sobagjo; Maftuchah Rochmanti; 'Ulaa Haniifah (Faculty of Medicine Universitas Airlangga, 2022)
Introduction: Cardiopulmonary Resuscitation (CPR) is an emergency lifesaving procedure performed when the heart stops beating. Basic Life Support (BLS) is the initial action to save life-saving conditions. BLS is one of the most important components in CPR. BLS greatly determines the fate of the next life-threatening victim. This study aimed to know the relationship of understanding CPR to readiness to do BLS for students of Faculty of Medicine, Universitas Airlangga, Surabaya.Methods: This was non-experimental study using the design of analytic and descriptive statistics. The sample of this study was the students of Faculty of Medicine, class of 2015, Universitas Airlangga, Surabaya and was taken by probability sampling method with a simple random sampling technique. Data retrieval was performed by giving a questionnaire to 100 respondents. This study was conducted in February 2019. The results of this study were then analyzed by SPSS using the Spearman test.Results: The results of this study showed that the most level of understanding CPR was in the good category with 56 people (56%), while the readiness to do BLS was mostly in the moderate category with 55 people (55%). Based on the results of statistical tests using the Spearman test, there was a relationship between the level of understanding CPR and the readiness to do BLS for students of Faculty of Medicine, Universitas Airlangga, Surabaya.Conclusion: There was relationship between the level of understanding CPR and the readiness to do BLS for students of Faculty Medicine, Universitas Airlangga, Surabaya.